2018
DOI: 10.1186/s10020-018-0016-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive fetal sex diagnosis in plasma of early weeks pregnants using droplet digital PCR

Abstract: BackgroundFetal sex determination is useful for families at risk of X-linked disorders, such as Duchenne muscular dystrophy, adrenal hypoplasia, hemophilia. At first, this could be obtained through invasive procedures such as amniocentesis and chorionic villus sampling, having a 1% risk of miscarriage. Since the discovery of cell-free fetal DNA (cffDNA) in maternal plasma, noninvasive prenatal testing permits the early diagnosis of fetal sex through analysis of cffDNA. However, the low amount of cffDNA relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 29 publications
(56 reference statements)
0
30
0
1
Order By: Relevance
“…The most common non‐invasive prenatal method for detecting foetal gender DNA in maternal plasma is qPCR 40 . Recently, ddPCR technology has been used to identify the Y chromosome at early gestational ages of pregnant women bearing male foetuses 41,42 . In the future, sensitive technologies will enable the prediction of the pathological phenotype of the unborn, which will thus avoid invasive diagnostic procedures for pregnant women, without risk to the foetus.…”
Section: Key Messages For Appropriate Genetic Counselling and Prenatamentioning
confidence: 99%
“…The most common non‐invasive prenatal method for detecting foetal gender DNA in maternal plasma is qPCR 40 . Recently, ddPCR technology has been used to identify the Y chromosome at early gestational ages of pregnant women bearing male foetuses 41,42 . In the future, sensitive technologies will enable the prediction of the pathological phenotype of the unborn, which will thus avoid invasive diagnostic procedures for pregnant women, without risk to the foetus.…”
Section: Key Messages For Appropriate Genetic Counselling and Prenatamentioning
confidence: 99%
“…A 2011 systematic review found that fetal sex determination by NIPT before 7 weeks gestation is unreliable . However, a more recent approach using ddPCR may lead to accurate fetal sex determination earlier than seven weeks of gestation . NIPT can also be used to indicate the presence of sex chromosome aneuploidies (SCAs) and other disorders of sex development .…”
Section: Nipt and Sex Determinationmentioning
confidence: 99%
“…hdfDNA'nın doğumdan 2 saat sonra, abortustan ise 24 saat sonra maternal dolaşımdan kaybolduğu gösterilmiştir. Bu durumun prenatal tanı için önceki gebelikten oluşabilecek kontaminasyonları engellediği görülmüştür (54). Fetal cinsiyetin belirlenmesinde gebeliğin 7. haftasında %70,9.…”
Section: Genometastaz Ve Hddnaunclassified